2014
DOI: 10.4236/jamp.2014.25009
|View full text |Cite
|
Sign up to set email alerts
|

Planck Constant as Adiabatic Invariant Characterized by Hubble’s and Cosmological Constants

Abstract: Within the framework of Einstein-Cartan-Shrödinger formalism with asymmetric connections, the Planck constant is calculated from the first principles (from geometry of our Universe), as the adiabatic invariant of electromagnetic field on the Riemann-Cartan manifold. The Planck constant, calculated with actually measured cosmological parameters, coincide with that one, measured in laboratory with precision up to the second digit. The non-local generalization of quantum theory is suggested. The fundamental sense… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
23
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 10 publications
8
23
0
6
Order By: Relevance
“…
In present paper we confirm our previous result [5] that the Planck constant is adiabatic invariant of electromagnetic field propagating on the adiabatically changed Finslerian manifold. Direct calculation from cosmological parameters gives value h=6x10(-27) (erg s).
…”
supporting
confidence: 92%
See 3 more Smart Citations
“…
In present paper we confirm our previous result [5] that the Planck constant is adiabatic invariant of electromagnetic field propagating on the adiabatically changed Finslerian manifold. Direct calculation from cosmological parameters gives value h=6x10(-27) (erg s).
…”
supporting
confidence: 92%
“…5) Recently we have published the paper in which we clearly points out the geometrical origin of the Planck constant [5]. In this paper we have shown that the Planck constant is adiabatic invariant of electromagnetic field on the adiabatically changed Finslerian manifold.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…A most visible mainstream effort to develop a theoretical framework for h is reported by Lipovka (2014). However, given the rigor and sophistry of the standard procedure, his final result makes very interesting comparison with the apparently dismissible mundane classical approach reported by Schreiber (2006).…”
Section: Planck Constant Hmentioning
confidence: 98%